(untitled) (Asian Journal of Social Science Studies, 2024)
This study aimed to examine the factors influencing individuals’ behavioral intentions to use hydraulic elevators through Structural Equation Modeling (SEM) analysis and assess their feasibility across five crucial aspects: Economic, Technical, Legal, Operational, and Scheduling. We found that perceived benefits, perceived risks, and social influence significantly impact behavioral intentions. The feasibility analysis results indicate that hydraulic elevators are economically, technically, and operationally viable, with mean scores of 0.68, 5.03, and 4.98, respectively. However, potential legal and scheduling challenges were identified, with mean scores of 0.33 for both aspects. The study’s implications suggest addressing individuals’ perceptions of benefits, risks, and social influence, as well as informing decision-makers about practical considerations for successful hydraulic lift implementation. Despite limitations, such as self-reported data and cross-sectional survey design, the study provides valuable insights into factors influencing behavioral intentions and feasibility considerations. Future research could explore longitudinal data and additional factors, such as environmental concerns, accessibility, and user experience.